Prevalence of thyroid disorders and thyroid autoantibodies among coastal communities of Malaysia (part of nationwide study of thyroid disorders in Malaysia) - Shahar , Mohammad Arif; Ghani, Liyana; Omar , Ahmad Marzuki; Loh , HH; Ooi , CP; MY, Yusniza; H, Zanariah; S, Subashini; Ibrahim, Luqman; Ab Wahab, Norasyikin; Sukor, Norlela; Md Zain, Rabizah; et al. (ASEAN Federation of Endocrine Societies, 2015)
Objectives To determine the prevalence of thyroid disorders and thyroid autoantibodies in the coastal communities of Malaysia. This study is part of a nationwide study looking into the prevalence of thyroid disorders.